2016
DOI: 10.1016/j.adro.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of automated 3-dimensional magnetic resonance imaging pancreas segmentation

Abstract: PurposeWith the advent of magnetic resonance imaging (MRI) guided radiation therapy, internal organ motion can be imaged simultaneously during treatment. In this study, we evaluate the feasibility of pancreas MRI segmentation using state-of-the-art segmentation methods.Methods and materialsT2-weighted half-Fourier acquisition single-shot turbo spin-echo and T1 weighted volumetric interpolated breath-hold examination images were acquired on 3 patients and 2 healthy volunteers for a total of 12 imaging volumes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Even better results have been seen for MRI‐based segmentation of pancreas. Guo et al reported the DSC > 0.83 using state‐of‐the‐art segmentation methods for T1‐weighted MRI of pancreas cancer patients . Our group is presently developing a texture‐based automatic contour‐correction method which is intended to be integrated with the method described in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even better results have been seen for MRI‐based segmentation of pancreas. Guo et al reported the DSC > 0.83 using state‐of‐the‐art segmentation methods for T1‐weighted MRI of pancreas cancer patients . Our group is presently developing a texture‐based automatic contour‐correction method which is intended to be integrated with the method described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al reported the DSC > 0.83 using state-of-the-art segmentation methods for T1-weighted MRI of pancreas cancer patients. 22 Our group is presently developing a texturebased automatic contour-correction method which is intended to be integrated with the method described in this study. Preliminary results show the contour-correction method is capable of achieving high-contour accuracy (DSC = 0.88 AE 0.03) with T1-weighted noncontrast MRIs.…”
Section: Discussionmentioning
confidence: 99%
“…The most straightforward approach is to derive the position information directly from the MR image. Often used in this case is autocontouring, in which the tumor or organ is automatically delineated [202][203][204][205][206][207][208][209][210]. Alternative methods include template matching, in which a template shape, for example of an organ or tumor, is located on the dynamic MR images [175,177,211,212], artificial neural networks [175,178] and nonrigid image registration [157].…”
Section: Tracking and Motion Modelingmentioning
confidence: 99%
“…Later, Gou et al. developed a novel dictionary learning (DL) method to segment based on T2W half-Fourier acquisition single-shot turbo spin-echo (HASTE) and T1W volumetric interpolated breath-hold examination images (14). These methods were tested on three patients and two healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%